Dividendos como mecanismo de sinalização - Schwerz, Maicon Bazzan (Universidade do Vale do Rio dos Sinos, 2014)
This study tested the hypothesis that dividends (in this study were also considered the proceeds of Interest on Equity) transmit information using two approaches. The object of the analysis population consisted of the companies that were present at the Ibovespa index for the months of September to December 2013, a total of 73 shares of 67 companies. The behavior of firms in the period from 01/01/2005 to 31/12/2012 was observed. In the first approach were tested whether variations in the distribution of results (payment of dividends) actual changes in behavior indicate the results of the years following this change. To test the hypothesis that companies use up its distribution of dividends to signal future results, the test of independence were used, using the chi-square curve. The results indicate that companies use its distribution of dividends to signal future results, a significance level of 15 %, thus supporting the hypothesis that dividends convey information. In the second approach tests to see how investors interpret the variations in payments of dividends made by the companies were conducted. We tested how the market behaves before and after companies to change their policy of profit distribution. The announcement dividends date, and two other windows were defined, the first includes the date -1 and 0 and 1 (3 sessions) and the second window of 11 trading days including the date of disclosure of benefit distribution, to seek information leaks and to verify the possibility of arbitration the study window. The results indicated that there is a relationship between the policy of distribution of profits and stock returns.
Keywords: Hipótese da sinalização; Dividendos e política de proventos; Signaling hypothesis; Dividend and income policy; ACCNPQ::Ciências Sociais Aplicadas::Economia